Illegitimate Tax Avoidance and Rule XVI of Preliminary Title of Tax Code - Tarsitano, Alberto (2014)
The author analyzes a very important issue such as illegitimate tax avoidance. He begins by explaining the content of the concept of illegitimate tax avoidance, and also he points out the differences with other concepts like tax evasion and tax planning. Then, he comments the debate on the use of legal figures which doesn’t belong to Tax Law, in order to solve issue of illegitimate tax avoidance. Finally, he explains the scope and the application of the Peruvian general anti-avoidance rule stipulated in the Peruvian Tax Code.